Case report: Psychedelic-induced seizures captured by intracranial electrocorticography - Blond, Benjamin N.; Schindler, Emmanuelle A. D. (Frontiers in Neurology, 2023)
Classic psychedelics are currently re-emerging as therapeutic agents with unique clinical benefits; however, it is also important to recognize the adverse effects of this drug class. While the risk of seizures with this drug class is known, the literature is lacking in detail. We present a case of psychedelic mushroom-induced seizures in a person with refractory right temporal lobe epilepsy implanted with a responsive neurostimulation (RNS) system. A large increase in typical seizure frequency coincided with the ingestion of a large dose of the mushrooms. This is the first reported case of electrographically confirmed seizures associated with classic psychedelic drug use. With the surge of research and movements toward the clinical application of classic psychedelic compounds, the risk for drug-induced seizures should be considered, including factors such as a history of epilepsy and drug doses and regimens.